Effective organizational functioning capacity needs of rural advisory service networks: A Delphi study - Lamm, Kevan W.; Lamm, Alexa J.; Davis, Kristin E.; Powell, Alyssa; Bommidi, Jyothi Swaroop (Association for International Agricultural and Extension Education, 2021)
This study expands on previous research within an international extension context with a particular focus on identifying the capacities associated with effective organizational functioning. A panel composed of 31 experts participated in a three-round Delphi process and identified a list of 38 specific capacities associated with effective organizational functioning related to extension networks. Among the 38 specific items, five primary themes emerged: (1) an extension network should be transparent about its policies, procedures, and organizational intent; (2) knowledge sharing and collaboration within an extension network is critical; (3) general policies and management guidelines should be in place; (4) the development and maintenance of intentional, long-term relationships with various actors in extension, including stakeholders, policy-decision makers, and the private sector is critical; (5) reasonable expectations and guidelines should be established for both extension network officers and network members. The study’s results provide a guide within which extension networks and organizations may evaluate current capacities from both a developmental and strengths perspective.